A PRELIMINARY STUDY ON THE ECOLOGY OF THE CORAL REEF OF POMBO ISLAND - Sumadhiharga, Ono Kurnaen (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
A preliminary study on the ecology of the coral reef of Pombo Island was carried out in 1975. Pombo Island has a characteristic of an atoll and is considered a good habitat for coral and fish, including live-bait fish of commercial importance,Â Spratelloides delicatulus. Non-planktonic organisms collected consist of 39 species of corals, 56 species of molluscs, 17 species of echinoderms, 130 species of fishes and a number of crustacean species.Some ecological factors such as bottom condition, turbidity, temperatures, light intensity, and freshwater dilution are described. Population and distribution of corals and coral fishes are discussed.